Correlations between corneal biomechanical properties measured with the ocular response analyzer and icare rebound tonometry - Jorge, Jorge (2008)
Purpose: To investigate the biomechanical properties of the normal cornea, and correlate them with central and peripheral corneal thickness and age. Methods: Seventy-six right eyes of volunteers were measured with Ocular Response Analyzer (ORA), ICare rebound tonometry and an ultrasound pachymeter at corneal center and at 4 mm from corneal center in the nasal and temporal directions. Results: ICare readings were significantly correlated with central and peripheral corneal thickness and corneal biomechanical properties. Corneal resistance factor was the biomechanical parameter with the higher correlation with ICare IOP values. ICare tonometry at center and Goldmann equivalent IOP obtained with ORA were significantly higher for thicker than thinner corneas (p<0.05). IOP compensated for corneal properties with the ORA was lower than the remaining IOP values measured in the study. Higher correlation was found between Goldmann equivalent IOP with ORA and ICare IOP values. Conclusions: Intra-ocular pressure values obtained with the rebound tonometer are higher in thicker corneas and are positively correlated with biomechanical corneal parameters, namely corneal resistance factor. Although corneal thickness plays a significant role in rebound tonometry, elastic and viscous properties of the cornea seem to play a significant role in the interaction of the tonometer probe with the ocular surface. However, the mechanism behind this process is presently unknown.